The Relevance of Restorative Justice in Reducing Overcapacity in Correctional Institutions for Male and Female Prisoners - Kurnia Dewi Anggraeny; Petrus Kanasius Kristiaga (Kosmik Hukum, 2025)
Correctional institutions in Indonesia are facing severe overcrowding, with the number of inmates far exceeding facility capacities. This issue is alarming as it leads to numerous negative consequences, including poor living conditions and difficulties in rehabilitation. One possible solution is adopting a restorative justice approach, which shifts the focus of the criminal justice system from punitive measures to reconciliation and rehabilitation, ensuring justice for both victims and offenders rather than relying solely on imprisonment. This study examines the factors contributing to overcapacity in Class IIB Sleman Penitentiary and Class IIB Wonosari Penitentiary while also assessing the relevance of restorative justice in addressing this issue. Using an empirical normative methodology with a sociological juridical approach, the research incorporates statutory and structural analyses to understand the root causes of overcapacity. The findings reveal several key factors behind the overcrowding problem, including the large jurisdiction and high population of Sleman, rising crime rates, the absence of detention centers in Sleman and Wonosari, high recidivism rates, the exclusion of certain offences from restorative justice eligibility, transfers of inmates from other correctional units, and inmates choosing to serve prison sentences instead of paying fines. Restorative justice is highly relevant in addressing this issue as it provides an effective alternative to imprisonment. By focusing on conflict resolution, offender rehabilitation, and victim involvement, restorative justice aligns with the evolving priorities of Indonesia’s legal system. Implementing this approach more effectively could significantly reduce overcrowding in correctional facilities while simultaneously ensuring justice for victims, offenders, and society as a whole.